Conjugacy of Self-Adjoint Difference Equations of Even Order. (13th July 2011) - Hasil, Petr
Abstract : We study oscillation properties of2 n -order Sturm-Liouville difference equations. For these equations, we show a conjugacy criterion using thep -criticality (the existence of linear dependent recessive solutions at∞ and- ∞ ). We also show the equivalent condition ofp -criticality for one term2 n -order equations.